2002
DOI: 10.1302/0301-620x.84b7.13195
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the iliolumbar vein: A cadaver study

Abstract: We carried out a cadaver study of 16 iliolumbar veins in order to define the surgical anatomy. Two variants were found; a single vein at a mean distance of 3.74 cm from the inferior vena cava (11 of 16) and two separate draining veins at a mean distance from the vena cava of 2.98 cm for the proximal and 6.24 cm for the distal stem (5 of 16). Consistently, the proximal vein tore on attempted medial retraction of the great vessels. The mean length of the vein was 1.6 cm and its mean width 1.07 cm. Three stems we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
1
27
1
4
Order By: Relevance
“…Therefore, as suggested by Jasani and Jaffray (2002), the iliolumbar vein, which is part of the external vertebral venous plexus, is closer to a venous system than a single vein. In fact, the vertical component of the iliolumbar vein, which we called ILV, had an important diameter, which increased as it coursed downwards and can be double when it enters into the iliac veins.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, as suggested by Jasani and Jaffray (2002), the iliolumbar vein, which is part of the external vertebral venous plexus, is closer to a venous system than a single vein. In fact, the vertical component of the iliolumbar vein, which we called ILV, had an important diameter, which increased as it coursed downwards and can be double when it enters into the iliac veins.…”
Section: Discussionmentioning
confidence: 93%
“…One of the venous injuries is tearing of the iliolumbar vein (Baker et al, 1993;Tribus and Belanger, 2001;Jasani and Jaffray, 2002). Accidental cannulation of this vein can also occur as a result of misdirection of a catheter destined for the IVC (Chedid et al, 2005;De and Imam, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification and ligation of the iliolumbar vein in the early phase of the exposure has been recommended to prevent inadvertent avulsion of the vein off the vena cava later in the procedure 18 . A cadaveric study showed that there are variations in the anatomy of the iliolumbar vein, and the presence of multiple iliolumbar veins may increase the chance of inadvertent venous injury 19 . XLIF -the more lateral trajectory compared to that of ALIF does not require retraction of the great vessels for exposure.…”
Section: Discussionmentioning
confidence: 99%